Instabilities; shocks and turbulence in space and astrophysical plasmas - Gomez, Daniel Osvaldo (2018)
The dynamics of plasmas pervading the interplanetary and interstellar medium are often described within the frame of magnetohydrodynamics (MHD), which involves the coupling between flows and magnetic fields. This theoretical framework adequately models the large scale behavior of a number of processes taking place in these plasmas, such as the generation of magnetic fields by dynamo mechanisms, the impulsive release of magnetic energy in reconnection events or the complex dynamics of turbulent flows. However, there are physical phenomena at smaller spatial scales that cannot be explained within the framework of traditional MHD. Throughout this work we show that the inclusion of additional physical effects such as the Hall current or electron inertia, it becomes possible to describe phenomena such as the fine structure of some shocks or the recently observed deviations in the turbulent energy spectrum of the solar wind.